101 things every girl should know : expert advice on stuff big and small - Alberta, Jacque; Bokram, Karen, 1968- (Grand Rapids, Michigan : Zonderkidz, 2015)
A faith-based guide to taking charge and feeling confident in the face of today's preteen challenges is complemented by quizzes, journal prompts, and articles.
Keywords: Girls -- Life skills guides -- Juvenile literature; Girls -- Religious life -- Juvenile literature; Christian life -- Juvenile literature; Girls -- Life skills guides; Girls -- Religious life; Christian life; Girls -- Life skills guides; Girls -- Religious life; Christian life